Assessment of Cardiometabolic Risk Factors Among Type 2 Diabetes Mellitus Patients in Minna, North-Central Nigeria - Kester Awharentomah Digban , Eguagie Osareniro Osakue , Esther Ngozi Adejumo , Ayodele, Adelakun , Oluwakemi Anike Ladipo and Comfort Bosede Enitan , Seyi Samson Enitan (Sokoto Journal of Medical Laboratory Science)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with economic and global health concern. The aim of this study was to assess the cardiometabolic risk factors in Type 2 diabetes mellitus patients attending General Hospital Minna, North Central, Nigeria. We recruited total of 135 subjects being 80 (57 females, 23 males) T2DM patients and 55 (38 females, 17 males) non-diabetic individuals who served as controls. A semi-structured questionnaire was used to collect socio-demographic data. Anthropometric measurements were also taken as appropriate. Blood samples were collected from subjects after 10 hours of fasting to investigate biochemical parameters for cardiometabolic risk in the test subjects and controls. Results show that T2DM patients had higher values of total cholesterol, waist circumference, SBP, DBP, TG and HDL compared to the non-diabetic controls. It was observed that 35.5% of the total population (both experimental and control subjects) were prone to cardiometabolic risk factors with 60% being T2DM patients and majority being females. A significant 48.8% of T2DM patients had well managed glycaemic levels, while 51.2% had a poorly managed glycaemic level. Findings also showed that 57.5% of T2DM patients were dyslipidaemic, 70% had abdominal obesity, while 40% had systolic hypertension. The SBP, FBS, TC, VLDL, TG and TG:HDL ratio of T2DM patients was significantly higher than controls (p< 0.001) while the differences in WC, DBP, LDL and HDL between T2DM and controls were not statistically significant (p> 0.05). On account of management among the T2DM patients, the FBS, TG and 120 HDL values between the well managed and poorly managed patients were statistically significant (p< 0.001), while the WC, BP, HbA1c and HDL values were not significant (p< 0.05). The CMR pattern among well managed, poorly managed T2DM and controls show that the well managed had abdominal obesity with high TG:HDL ratio, while the poorly managed had systolic hypertension. Correlation of all variables with glycaemic levels show positive and highly significant in poorly managed T2DM patients. This study demonstrated that patients with type 2 DM have a higher risk for developing cardiovascular disease than non- diabetic subjects.